THE EVALUATION OF NATIONAL CADRE TRAINING PROGRAM (PKN) OF CENTRAL BOARD OF INDONESIAN MOSLEM STUDENT MOVEMENT (Evaluation Study of Kirkpatrick Model) - Ahmad Riduan (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
Abstract: This study aims to evaluate the implementation of the Training of national the members. This research was conducted in PB PMII. The methodology used is the evaluative research through the Kirkpatrick model includes four levels, namely; reaction, learning, behavior and result. The results showed that: (1) participants are satisfied with the service of the Committee in terms of infrastructure, material/curriculum, instructors, and schedule, (2) the participants mastered the training material which can be seen from the test results given the active as well as provide questions, attend any activity, (3) any change of behaviour for participants after returning to their respective regions as well as pedagogic competencies, personality, social, and professional, and (4) productivity increase with the presence of the module, the method of organization development and problem solving as well as improved performance through public speaking ability discipline, liveliness, new ideas, and ethics to NU. Based on the findings, it was concluded that this aspect of the reaction, learning, behavior and the result is already very good.